2021
DOI: 10.1007/s11150-021-09574-7
|View full text |Cite
|
Sign up to set email alerts
|

Does signaling childcare support on job applications reduce the motherhood penalty?

Abstract: There is substantial evidence that due to perceived childcare obligations, mothers are disadvantaged in labor markets. To what extent can childcare support ameliorate such a disadvantage? To answer this question, we ran a CV experiment in a large Indian city and examined whether indicating access to childcare support in a CV may offset the motherhood penalty associated with labor market entry. We randomly varied motherhood, as well as access to childcare in CVs sent to online applications for service sector jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…And the linkage between fertility and labor supply has important policy implications. Previous literature on the effect of fertility on labor market outcomes, in general, nd a negative effect for female -motherhood penalty, and a positive effect for male -breadwinner bonus (Angrist and Evans, 1996;Bedi, et Wu, 2022). But these studies focus on the effects for adults of childbearing age.…”
Section: Introductionmentioning
confidence: 99%
“…And the linkage between fertility and labor supply has important policy implications. Previous literature on the effect of fertility on labor market outcomes, in general, nd a negative effect for female -motherhood penalty, and a positive effect for male -breadwinner bonus (Angrist and Evans, 1996;Bedi, et Wu, 2022). But these studies focus on the effects for adults of childbearing age.…”
Section: Introductionmentioning
confidence: 99%
“…Such structures are required for two reasons: (1) for a better work-life balance for women (and men) and (2) for creating a socio-psychological climate in which it might be assumed by the recruiters and senior colleagues that women can take care of family (since gendered role assumptions will not change easily). A study using fictitious CVs in two industry sectors in Delhi found that indicating access to childcare in job applications partially reduces motherhood penalty (Bedi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%